2018
DOI: 10.3390/ijms19092554
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of 2,3,5,4′-Tetrahydroxystilbene-2-O-β-d-glucoside on Ovariectomy Induced Osteoporosis Mouse Model

Abstract: 2,3,5,4′-Tetrahydroxystilbene-2-O-β-d-glucoside (TSG), an active polyphenolic component of Polygonum multiflorum, exhibits many pharmacological activities including antioxidant, anti-inflammation, and anti-aging effects. A previous study demonstrated that TSG protected MC3T3-E1 cells from hydrogen peroxide (H2O2) induced cell damage and the inhibition of osteoblastic differentiation. However, no studies have investigated the prevention of ovariectomy-induced bone loss in mice. Therefore, we investigated the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 62 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…Diabetic patients have a higher risk of bone fractures (Kanazawa, 2015). Because our coworkers previously indicated that HSW hot water extract and its bioactive component THSG prevent bone loss in an ovariectomy-induced osteoporosis mouse model (Hwang et al, 2016; Kim et al, 2018b), this study was conducted to determine if HSW extract may prevent bone loss caused by diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic patients have a higher risk of bone fractures (Kanazawa, 2015). Because our coworkers previously indicated that HSW hot water extract and its bioactive component THSG prevent bone loss in an ovariectomy-induced osteoporosis mouse model (Hwang et al, 2016; Kim et al, 2018b), this study was conducted to determine if HSW extract may prevent bone loss caused by diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that Heshouwu ethanol extract attenuates hyperglycemia and hyperinsulinemia in diet-induced obese mice (Choi et al, 2018). Hwang et al (2016) and Kim et al (2018b) reported that Heshouwu hot water extract and tetrahydroxystilbene glucoside (THSG), which is a bioactive compound of Heshouwu, prevent bone loss in estrogen deficient mice. Zhang et al (2019) recently reported that THSG protects against diabetes-induced osteoporosis in mice with streptozotocin (STZ)-induced diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Through prompt the biosynthesis of enzymes relating to mitochondrial energy conversion, Dioscorea optimizes energy metabolism under hypoxia and resists apoptosis to keep cell “young” [33]. Component of Polygonum multiflorum has many pharmacological activities including antioxidant, anti-inflammation, and anti-aging effects [34]. Codonopsis pilosula can acts as an immunoregulator which inhibits too strong inflammation to weaken apoptosis and gliosis [35].…”
Section: Discussionmentioning
confidence: 99%
“…From this viewpoint, asthma treatment using PM extract has the potential to cause various side effects. Nevertheless, PM has various biological effects [13,14,15,16] and 2,3,5,4′-tetrahydroxystilbene-2-O-β- d -glucoside (TSG) as a main single compound has anti-inflammatory effects [14] and anti-osteoporosis effect [13]. In the present study, we investigated the effects of TSG on asthma as one of the inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological studies have emphasized the benefits of PM in the treatment of a variety of diseases, such as cancer, diabetes, alopecia, atherosclerosis, and neurodegenerative diseases [11]. 2,3,5,4′-tetrahydroxystilbene-2-O-β- d -glucoside (TSG) is known as a major active single compound of PM [12], and presents a variety of biological effects, such as anti-osteoporosis [13], anti-inflammation [14], kidney protection [15], anti-cancer [16], and liver protection effects [17]. However, Lei et al reported that PM extracts have hepatotoxicity [18], and this is probably due to the cis isomer of TSG [19].…”
Section: Introductionmentioning
confidence: 99%